2017
DOI: 10.1080/09638288.2016.1275043
|View full text |Cite
|
Sign up to set email alerts
|

Aiming for a healthier life: a qualitative content analysis of rehabilitation goals in patients with rheumatic diseases

Abstract: The rehabilitation goals of the patients with rheumatic diseases were found to be wide-ranging, with healthy lifestyle as the most prominent focus. Goal content changed between admission to, and discharge from, rehabilitation stays. Implications for rehabilitation Rehabilitation goals set by patients with rheumatic diseases most frequently concern healthy lifestyle changes, yet span a wide range of topics. Patient goals vary by gender and are influenced by the profession of the health care worker involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…For instance, if one person has kindness as a strength, the app could suggest for him or her to do something kind to a neighbor today. Most of these exercises were based directly on strengths exercises found in academic and popular literature [ 10 , 14 , 82 - 84 ] or related to items reported by participating patients in earlier related studies [ 16 ]. The wording and content of these exercises were iteratively refined during the user evaluations of the app.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, if one person has kindness as a strength, the app could suggest for him or her to do something kind to a neighbor today. Most of these exercises were based directly on strengths exercises found in academic and popular literature [ 10 , 14 , 82 - 84 ] or related to items reported by participating patients in earlier related studies [ 16 ]. The wording and content of these exercises were iteratively refined during the user evaluations of the app.…”
Section: Resultsmentioning
confidence: 99%
“…Patients' goals may involve, for example, pain relief, changing of lifestyle, gaining of knowledge and disease management. 50 What is of importance to a patient can be difficult to formulate and score in the PSFS. In the primary care study in Copenhagen, the PSFS was introduced for patients receiving rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a main purpose of the goals, to provide focus and direction for the rehabilitative efforts, may have been disturbed. A previous study of the rehabilitation goals of patients who received the add‐on intervention revealed that although most patients had goals concerning a healthy lifestyle, some patients formulated a large number of goals that covered a wide range of poorly connected topics . The pursuit of multiple diverging goals scatters the attention and may lead to becoming overwhelmed or to conflicts between personally valued goals regarding the priority and direction of further efforts .…”
Section: Discussionmentioning
confidence: 99%
“…The pursuit of multiple diverging goals scatters the attention and may lead to becoming overwhelmed or to conflicts between personally valued goals regarding the priority and direction of further efforts . Such conflicts may disturb focus and motivation, hamper progress of goal‐directed activity, and thus reduce the possibility of goal achievement . Further, failure to achieve goals may again influence HRQoL .…”
Section: Discussionmentioning
confidence: 99%